Feasibility study of Ulva sp. (Chlorophyta) intensive cultivation in a coastal area of the Eastern Mediterranean Sea. (1st April 2019) - Chemodanov, Alexander; Robin, Arthur; Jinjikhashvily, Gabriel; Yitzhak, Dror; Liberzon, Alexander; Israel, Alvaro; Golberg, Alexander
Abstract: Increasing biomass production yields is a critical challenge for macroalgae biorefineries. The continuous tumbling and mixing of free‐floating algae through water or airflow has been shown to increase the productivity of algae in land‐based cultivation systems. This approach has not been tested thoroughly in offshore cultivation. We report, here, a field feasibility study on the increase in green macroalga Ulva sp. growth rates in offshore cages, achieved by the combined effect of tumbling and mixing of the algae using influxes of water and air. The experimental system was tested in a shallow coastal area in central Israel, in the eastern Mediterranean Sea. A maximum daily growth rate of 19.2%, areal productivity of 33.72 g dry weight (DW) day −1 m −2, and volumetric yields of 37.78 g DW day −1 m −3, together with 38.47 ± 0.01% ash and 5.28% protein content on a dry matter basis were achieved in the cages with intensified cultivation in the first week of May 2017. Our study shows that cultivation with tumbling and mixing of biomass with air, and water exchange with the environment is a feasible method to increase Ulva sp. biomass productivity offshore. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd